Treatment of autoimmune encephalitis with immune based therapies. Issue 5 (8th May 2017) - Dowland, Francesca; Swayne, Andrew; Bhuta, Sandeep; Sabet, Arman; Broadley, Simon
Abstract : Objectives: To present three patients with autoimmune encephalitis seen at a tertiary neurology centre with response to immune based therapy including rituximab. Cases: The first patient is a 24 year old female who presented with propriospinal myoclonus. MRI brain showed demyelination and autoantibodies were negative. Following minimal improvement with steroids and apheresis, there was significant improvement with rituximab. The second patient, a 63 year old male who presented at different times with confusion, aphasia, weakness and incontinence. MRI brain was unremarkable. Anti-GAD antibodies with intermediate levels of 175 and 225, as well as anti-TPO and anti-thyroglobulin antibodies, were positive. There was partial improvement and stabilisation with intravenous gammaglobulin, but more significant improvement following rituximab. The final patient is a 17 year old female who presented with headache, progressive weakness, ataxia and paraesthesia, leading to obtundation and admission to ICU. MRI brain showed multiple large, predominantly white matter lesions. Treatment with steroids and apheresis was associated with near complete recovery. Conclusions: The field of neuro-immunology has seen a plethora of newly discovered autoantibodies, yet there remain a significant number of patients, with features suggestive of an antibody-mediated pathophysiology, with inconclusive or negative results. These three patients highlight the potentially valuable role of immune-therapy and particularly B-cell depletion therapies in the setting of neuroimmunological disease when antibody tests are negative or of uncertain significance. These therapies are expensive and there is a need to consider appropriate trial methodologies in this setting. There is also a need for the continued search for novel autoantibodies.